FAKTOR - FAKTOR YANG MENYEBABKAN TUMBUHNYA LOYALITAS KARYAWAN PADA KLINIK PRATAMA LEKAS SEHAT - Zulia Eka Pusparini; Jumawan; Fahmi Sahlan; Indah Rizki Maulia; Rycha Kuwara Sari (IJESM Indonesian Journal of Economics and Strategic Management, 2025)
In healthcare organizations, employee loyalty has become a crucial factor for the enterprise's long-term sustainability. This study aims to clarify the factors that contribute to employee loyalty through a qualitative research approach. Analyzing interview transcripts, it identifies key elements that promote loyalty, such as a supportive work environment, appropriate compensation for effort, and a healthy balance between professional and personal life. Additionally, opportunities for self-development and a strong sense of being valued are also significant. However, enhancements in clinic facilities and adjustments in work systems are necessary to foster employee growth and loyalty. The findings provide valuable insights for management to elevate service quality and operational efficiency by fostering increased employee loyalty.